Incidence of Renal Involvement in Malaria in Children of Odisha. (1st November 2013) - Padhi, Rajesh Kumar; Mishra, Soumya
Abstract : About 500 million people suffer from malaria leading to death in 2-3 million cases every year, of which about 1 million are children. Horstman et al., 1985, and Weber et al., 1991, demonstrated an acute renal failure as a well-described complication of Plasmodium falciparum malaria in nonimmune adults and a major contributor to their mortality. In children, renal failure, though not very common, has become a rising issue leading to death. This study aims at determining the incidence of renal complication in malaria cases reported in children of Odisha. 108 cases of malaria who were admitted to Department of Paediatrics, SCB Medical College and Hospital and Sardar Vallab Bhai Patel Post Graduate Institute of Paediatrics, Cuttack, Odisha, India during the period from July 2006 to November 2008 were included in the prospective study. Extensive investigations were carried out to check for renal involvement in these cases. 50.9% of cases showed some form of renal involvement, most of which were recorded in age group of 5–10 years. Overall, males had a higher incidence than females. 62.7% of total cases infected with P. falciparum showed renal involvement though mixed infections with both P. falciparum and P. vivax had 100% renal involvement.